Architecture, empire, orientalism - Çelik, Zeynep. (İstanbul)
431, [1] sayfa, [16] sayfa resim, harita, plan
Keywords: “Architecture, Empire, Orientalism: Essays on Late Ottoman and French Colonial Practices In this volume, Zeynep Çelik brings together her articles based on meticulous archival work since the early 1980s, keeping in mind the question about the constitution of archives. The essays in the first part of the book offer historiographical analyses and experiment with methods, while the second part presents hands-on case studies ranging from Cairo, Istanbul, Aleppo, and Jerusalem to Ankara, Tunis, and Fez, covering the nineteenth and twentieth centuries. Çelik's essays expand the mainstream architectural history to include “non-traditional” topics and are linked by a theoretical perspective inspired by postcolonial scholarship and the critique of orientalism, and based on interdisciplinary empirical research” --